SINESTESIA DALAM FACEBOOK - Novia, Rijel; Auzar, Auzar; Faizah, Hasnah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This article discusses synesthesia on facebook. The purpose of this study is to describe the pattern of synesthesia, describing the change in meaning and describing the function of synesthesia. This research is a descriptive qualitative research with documentation method. Sources of data come from the status of Facebook user accounts taken from June to September with a total of 102 data. Based on the research, synesthesia of the sensory absorption patterns found on facebook includes cool, soft, rough, sharp, sweet, bitter, smooth, high, dim, low, flat, sour and tasty. And there are 8 patterns in the five senses found on facebook found, namely: (1) taste senses to the auditory senses as much as 36 data, (2) sensory taste to the auditory sense as much as 12 data, (3) sense of smell to the auditory sense as much as 1 data , (4) senses of taste to the visual sense as many as 42 data, (5) sense of taste to the sense of sight as much as 5 data, (6) sense of sight to the auditory sense as much as 4 data, (7) sense of taste to sense of smell as much as 1 data, and (8) taste senses to the sense of smell as much as 1 data. From the eight sensory patterns found on facebook, it turns out that the data patterned senses tasting into the senses are the most common among the other sensory patterns, as many as 42 data. This exchange between sensory responses to one another turns out to be strongly influenced by the context of the sentence. Likewise with changes in meaning, and the function of synesthesia is strongly influenced by the context of the sentence.Keywords: synesthesia, and, facebook